Sportivnaja elektronejromiografija - Prjanisnikova, O. A.; Gorodnicev, R. M.; Gorodniceva, L. R.; Tkacenko, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was to reveal the features of the electroactivity of skeletal muscles at the performance of complex movements on coordination and the use of the data received for the optimization of technical and power training of wrestlers.